THE PHENOMENON OF A SCIENTIFIC DISCIPLINE - Natalya I. Kuznetsova (Высшее образование в России)
The article highlights the process of formation of scientific disciplines. Referring to the broad historical material, the author shows that this process is a manifestation of self-organization of the scientific community. The success of the emergence of a new discipline is associated with the advancement of a collector program (program systematization of knowledge), not research program. The collector program provides the cognitive institutionalization of a particular area of research practice. The training courses are based on the collector programs, they have been being developed with the purpose to broadcast cognitive experience, including the «tacit knowledge», without which any professional scientific activities is impossible.